Infinitum : an afrofuturist tale - Fielder, Tim (Amistad, an imprint of HarperCollinsPublishers, 2021)
"An Afrofuturist graphic novel that presents a new universe, tackling racism, classism, and gender equality while exposing ancient mysteries"--